Intelligent Buoy System (INBUS): Automatic Lifting Observation System for Macrotidal Coastal Waters - Jin, Jae-Youll; Dae Do, Jong; Park, Jin-Soon; Park, Jun Seok; Lee, Byunggil; Hong, Sung-Doo; Moon, Sung-Ju; Hwang, Keun Choon; Chang, Yeon S. (Frontiers in Marine Science, 2021)
The west coast of South Korea is characterized by a wide macrotidal area with a maximum tidal range of ~10 m. The sea surface elevation changes according to the tidal phase, which can lead to significant changes in the vertical structures of the physical, chemical, and biological properties of the water column, especially when the interaction by waves and/or the freshwater and sediment input from the river increases. Under such conditions, it is difficult to carry out continuous and consistent measurements of the vertical structures of the water qualities using a conventional observation system that is fixed onto the seabed or sea surface because the thickness of the water column constantly changes. Based on the demand for long-term observations of the vertical structures of the water properties in macrotidal environments, the Intelligent Buoy System (INBUS) was developed by the Korea Institute of Ocean Science and Technology. The INBUS is a buoy equipped with an instrument frame, which is similar to other buoys that are fixed to the sea surface. During every measurement, INBUS detects the water depth and sends the frame down to the bottom to measure the water quality at every vertical level set up in the system. For example, if N levels are set in the INBUS, the water depth of each measurement is divided by N layers and the instruments in the lifting frame measure the water properties of each of the N layers while they are descending to the bottom. Based on this procedure, the vertical structure of the water column can be consistently measured in N layers regardless of changes of the water depth due to tides and waves. The lifting and measuring process is automatically controlled by INBUS once it is set up in the system. In addition, because INBUS allows bidirectional communication through code division multiple access (CDMA), the system can be controlled by stations on land. In case the CDMA communication is not working under extreme wave conditions or the buoy is lost due to the collision with a ship, the location of the INBUS can be tracked by low-earth orbit satellites.